The structure and seismicity of Icelandic rifts - Green, Robert G. (2016)
Three-fi fths of the Earth’s crust has been built at oceanic spreading centres in the last 160 million years. To explore crustal extension processes and the architecture of these constructive plate boundaries I have studied the oceanic rift in Iceland. Here the Mid Atlantic Ridge is anomalously elevated above sea level and thus easier to instrument. I have deployed and operated a dense network of seismometers in the remote volcanic highlands in central Iceland, and used the passive seismic data collected from this network to explore crustal structure and volcanic processes in the extensional rift zones.